Parameter optimization CCPP and coolant system gas turbine - Клер, Александр Матвеевич; Захаров, Юрий Борисович; Потанина, Юлия Михайловна (Eastern-European Journal of Enterprise Technologies, 2013)
Today most researchers optimize the parameters of cycles in combined cycle power plants without detailed calculations of the gas turbine flow path, which often involves separate optimization of the steam cycle and the gas turbine parameters, including the parameters of the gas turbine flow path that are usually known beforehand. This paper is the first to suggest a technique for coordinated optimization of combined cycle power plants, where both the parameters of the steam cycle in the combined cycle power plant and the parameters of the gas turbine, including the design parameters of its flow path, are optimized simultaneously. Based on the proposed technique we carried out optimization studies on the combined cycle power plant with optimum capacity. We also made optimization studies on the combined cycle power plant using the classical separate technique. The developed technique suggests an approach to the estimation of investment in gas turbine plants. This technique can be used to conduct studies on gas turbine plants and combined cycle power plants for different types and ways of cooling the gas turbine flow path. The presented data of optimization calculations show the advantages of optimizing combined cycle power plants using this technique as compared to the methods, where gas turbine and the steam cycle of the combined cycle power plant are optimized separately. The economic effect of applying the proposed technique is described.